2010
DOI: 10.1021/cb100321m
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Homeostasis Modulation Enhances the Amenability of L444P Glucosylcerebrosidase to Proteostasis Regulation in Patient-Derived Fibroblasts

Abstract: Gaucher's disease is caused by deficiency of lysosomal glucocerebrosidase (GC) activity and accumulation of GC substrate, glucosylceramide. A number of point mutations in GC encoding gene have been reported to destabilize the enzyme native structure, resulting in protein misfolding and degradation. Particularly, the L444P GC variant, often associated with neuropathic manifestations of the disease, is severely destabilized and immediately degraded, resulting in complete loss of enzymatic activity. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 61 publications
3
44
0
Order By: Relevance
“…Mutations in glucocerebrosidase may destabilize its structure, resulting in misfolding and degradation of the enzyme (for review, see Vitner et al, 2010). The accumulation of glucosylceramide results in Ca 2ϩ release through ER RyR, and blockade of RyR can restore normal folding of mutant glucocerebrosidase in fibroblasts from patients with Gaucher disease (Wang et al, 2011). Likewise, Ong et al (2010) found that increasing ER Ca 2ϩ levels by reducing ER Ca 2ϩ efflux through RyR (with the use of antagonists or RNA interference) or by enhancing ER Ca 2ϩ influx through SERCA2b overexpression increased glucocerebrosidase activity in fibroblasts from patients with Gaucher disease.…”
Section: B Lipid Storage Disorders: Gaucher Sandhoff and Niemann-pmentioning
confidence: 99%
“…Mutations in glucocerebrosidase may destabilize its structure, resulting in misfolding and degradation of the enzyme (for review, see Vitner et al, 2010). The accumulation of glucosylceramide results in Ca 2ϩ release through ER RyR, and blockade of RyR can restore normal folding of mutant glucocerebrosidase in fibroblasts from patients with Gaucher disease (Wang et al, 2011). Likewise, Ong et al (2010) found that increasing ER Ca 2ϩ levels by reducing ER Ca 2ϩ efflux through RyR (with the use of antagonists or RNA interference) or by enhancing ER Ca 2ϩ influx through SERCA2b overexpression increased glucocerebrosidase activity in fibroblasts from patients with Gaucher disease.…”
Section: B Lipid Storage Disorders: Gaucher Sandhoff and Niemann-pmentioning
confidence: 99%
“…This was demonstrated by enhancing the cellular folding capacity of patient-derived cells through the use of small molecules that influence general cellular folding pathways that maintain protein homeostasis, such as chaperones and the proteasomeubiquitin system (8,9) or Ca 2ϩ homeostasis (10,11). Mechanistic studies conducted to investigate changes in the cellular folding network that enhance mutated GC activity led to the observation that augmenting the pool of mutated GC in the ER is critical to promote rescue of its folding and trafficking (10,11).…”
Section: Lysosomal Storage Disorders (Lsd)mentioning
confidence: 99%
“…This was demonstrated by enhancing the cellular folding capacity of patient-derived cells through the use of small molecules that influence general cellular folding pathways that maintain protein homeostasis, such as chaperones and the proteasomeubiquitin system (8,9) or Ca 2ϩ homeostasis (10,11). Mechanistic studies conducted to investigate changes in the cellular folding network that enhance mutated GC activity led to the observation that augmenting the pool of mutated GC in the ER is critical to promote rescue of its folding and trafficking (10,11). Specifically, we demonstrated that an increase in mutated GC activity correlates with (i) up-regulation of the main ER chaperone BiP, which is known to enhance ER retention and prevent ERAD of misfolding intermediates (12), and (ii) up-regulation of GBA, most likely caused by UPR-induced changes in lipid metabolism (10,11).…”
Section: Lysosomal Storage Disorders (Lsd)mentioning
confidence: 99%
See 2 more Smart Citations